다문화가정 모친의 자녀 구강건강관리 관련요인 - 김미; Mi Kim; 조영식; Young-sik Cho (Han'guk Ch'iwisaeng Hakhoe chi, 2018)
Objectives: The purpose of this study was to identify the factors affecting the oral health behavior of mothers in multicultural families and the oral health management of children. Methods: The subjects were 303 mothers in multicultural families having children in childhood. To verify the validity of the outcome, a factorial analysis was conducted. To examine differences in the outcome according to socio-demographic characteristics, a one-way ANOVA was used, and the hypothesis was tested through a multiple regression analysis. Results: According to the results, it was found that severity, self-efficacy, sensitivity, and multicultural disability that show attitudes had significant impact on the mother’s oral health behavior. Moreover, it was found that self-efficacy, sensitivity, and the mother’s oral health behavior that show attitudes had significant impact on the children’s oral health management. Conclusions: Based on the results of this study, it would be necessary to increase the interest in mother-and-child oral health, developing a mother-and-child oral health education program targeted toward the oral health of the mothers and children in multicultural families. Moreover, it is essential to educate mothers in multicultural families in order to increase their sense of responsibility toward their children’s oral health management, aiming to promote knowledge and to change attitudes and behavior.